Viabilitas dan Vigor Benih Kacang Tanah (Arachis hypogaea L.), Kacang Hijau (Vigna radiata (L.) R. Wilczek), dan Jagung (Zea mays L.) pada Temperatur dan Tekanan Osmotik Berbeda - Zidny Fatikhasari; Intani Quarta Lailaty; Dian Sartika; Muhammad Aldian Ubaidi (Institut Pertanian Bogor, 2022)
Viability and vigor are components of seed quality assessment which are influenced by internal and external factors of the seed, i.e., salinity and temperature. Salinity is related to the interaction between osmotic pressure and seed germination. This study used 3 types of seeds, they are peanuts (Arachis hypogaea L.), mung bean (Vigna radiata (L.) R. Wilczek), and corn (Zea mays L.). The purposes of this study were to determine seed viability by using Triphenyl tetrazolium chloride (TTC), to analyze the effects of different osmotic pressures and temperatures on seed viability and vigor. Peanut seed viability test was conducted by using 1% TTC solution. Testing the effect of osmotic pressure on seed viability and vigor was conducted by using various concentrations of NaCl (0.01 M; 0.05 M; 0.5 M; 0.1 M; 1 M). The germination test of the three seeds was conducted by using temperatures of 30°C and 35°C, each with three replications. The test parameters measured included germination, germination rate, germination speed index, vigor index, simultaneous growth, and the speed of seed growth. The results showed that TTC solution was effectively used to determine seed viability. Mung bean had the highest germination rate, LP, IKP, IV, simultaneous growth, and speed of seed growth compared to the other tested seeds in all salinity and temperature treatments. The 30 ⁰C temperature treatment resulted in the best viability and seed vigor for the three tested plants. Treatments of temperature and salinity affect the quality of the three plant seeds which can then be used to determine the quality of peanut, mung bean, and corn seeds. Keywords: germination, salinity, triphenyl tetrazolium chloride, viability, vigour